2016
DOI: 10.1186/s40462-016-0079-4
|View full text |Cite
|
Sign up to set email alerts
|

Caribou, water, and ice – fine-scale movements of a migratory arctic ungulate in the context of climate change

Abstract: BackgroundFreshwater lakes and rivers of the Northern Hemisphere have been freezing increasingly later and thawing increasingly earlier during the last century. With reduced temporal periods during which ice conditions are favourable for locomotion, freshwater bodies could become impediments to the inter-patch movements, dispersion, or migration of terrestrial animals that use ice-covered lakes and rivers to move across their range. Studying the fine-scale responses of individuals to broad-scale changes in ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 55 publications
2
47
0
1
Order By: Relevance
“…Some, such as the Dolphin and Union population and Peary caribou, migrate across the sea ice between seasonal ranges (Miller et al 1977;Poole et al 2010), whereas others prefer moving across frozen lakes and rivers for ease and directional persistence of movement and increased visibility of predators (Pruitt 1959;Sharma et al 2009;Leblond et al 2016). Warming surface temperatures will, and already are, changing the annual timing of both sea ice (Poole et al 2010) and freshwater ice (Latifovic and Pouliot 2007;Sharma and Magnuson 2014) formation and break-up.…”
Section: Movement Migration and Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some, such as the Dolphin and Union population and Peary caribou, migrate across the sea ice between seasonal ranges (Miller et al 1977;Poole et al 2010), whereas others prefer moving across frozen lakes and rivers for ease and directional persistence of movement and increased visibility of predators (Pruitt 1959;Sharma et al 2009;Leblond et al 2016). Warming surface temperatures will, and already are, changing the annual timing of both sea ice (Poole et al 2010) and freshwater ice (Latifovic and Pouliot 2007;Sharma and Magnuson 2014) formation and break-up.…”
Section: Movement Migration and Distributionmentioning
confidence: 99%
“…They reported that caribou tended to select ice and avoided water when crossing or moving near large water bodies and that ice increased caribou movement rates. Simulations predicted that for the Rivière-aux-Feuilles herd as much as 36% of ice crossings during the spring and fall migrations could be lost by 2070 (Leblond et al 2016). Loss of ice crossings would likely increase the distance travelled during migrations because the migratory path would skirt water bodies rather than cross them (Leblond et al 2016), thereby increasing the energetic cost of migration.…”
Section: Movement Migration and Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some species such as the Arctic fox have specialized into using the seasonal sea ice as a foraging platform (Lai et al 2015) and can travel thousands of kilometres over land and ice (Tarroux et al 2010). Migrating caribou in northern Quebec regularly cross large lakes when they are frozen (Leblond et al 2016), and spring ice breakup is a critical time when impassable barriers, such as flooded rivers, can arise even for strong swimmers like caribou. Ice cover may thus have important impacts on daily movements, seasonal migrations, and dispersal events of tundra wildlife, with far-reaching consequences on their foraging behavior, population dynamics, and species distributions.…”
Section: Mechanical Resistance-2: Impact Of Freeze-thaw or Rain-on-snmentioning
confidence: 99%